It is given that a , b , and c are non-negative integers satisfying the equation:
a + b + c = a b + b c + c a = 3 a b c
Find the sum of all the possible values of a b c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
That's a very nice solution. Slight typo/omission - I think you've divided the discriminant through by p without considering the case p = 0 (which gives a valid solution, but not a very interesting one!).
Without loss of generality, let a ≤ b ≤ c .
If a = 0 , we have b + c = b c = 0 ; so b = c = 0 as well.
If a = 1 , we have 1 + b + c = b + c + b c , so that b c = 1 and b = c = 1 ; checking the remaining equation, we see that this is indeed a solution.
Now assume a > 1 . Note that a b ≤ c a ≤ b c , so a b + b c + c a ≤ 3 b c < 3 a b c ; hence no other solutions exist.
Hence the total of all valid a b c is 1 .
Hi. I have got an alternative solution. However I couldn't post it as a solution as some glitch happened and it said incorrect when I typed answer is 1. Anyway here it is. We are given that a, b, c are non negative integers satisfying the equations. a+b+c=ab+bc+ca=3abc. So dividing the second and third parts by abc, we get 1/a+1/b+1/c=3. If a,b, c are positive integers, 1/a, 1/b, 1/c are less than or equal to 1. Equality arises only when a,b,c=1. Hence a,b,c are all 1 as their sum is strictly less than 3 otherwise. Hence, abc=1. So the final answer is 1
Sorry a b and c
best solution posted by nitin kumar!!
We can write 3abc(a+b+c)=(ab+bc+ca)². Now let bc=x,ca=y,ab=z, our equation transforms to (x+y+z)²=3(xy+yz+zx)=>x²+y²+z²-xy-yz-zx=0. Clearly, x=y=z=>a=b=c.
Let us start by solving for c in terms of a and b :
3 a b − 1 a + b = c = 3 a b − ( a + b ) a b ⇒ ( 3 b − 3 b 2 − 1 ) a 2 + ( 3 b 2 − b ) a − b 2 = 0 .
Solving for a via the Quadratic Formula gives:
a = 2 ( 3 b − 3 b 2 − 1 ) ( b − 3 b 2 ) ± ( 3 b 2 − b ) 2 − 4 ( 3 b − 3 b 2 − 1 ) ( − b 2 ) = 2 ( 3 b − 3 b 2 − 1 ) ( b − 3 b 2 ) ± − 3 b 4 + 6 b 3 − 3 b 2 = 2 ( 3 b − 3 b 2 − 1 ) ( b − 3 b 2 ) ± − 3 b 2 ( b − 1 ) 2 (i).
The only way (i) will be real-valued is for b = 0 , 1 , which in turn yield a = 0 , 1 and c = 0 , 1 respectively. These ultimately produce the two products:
a b c = 0 3 or a b c = 1 3 ⇒ 0 + 1 = 1 .
Why will (i) be real valued only for b=0,1?
Log in to reply
Because the above discriminant expression is strictly non-positive for all real b. If b does not equal 0 or 1 (in order to zero-out the negative square-root), then the value of a will end up as a complex number. I would suggest stating 'Non-zero, real integers' if the problem statement needs additional clarification.
A valid proof is necessary
Log in to reply
I disagree with your comment. The algebra above is soundly presented and provides an alternative solution to the previous ones. Please feel free to provide a proof-based solution of your own if you'd like.
Yes.That was the proof i was expecting from you!!!
Now, since you have proved it this solution is the simplest solution!!!
Congrats!!!
Problem Loading...
Note Loading...
Set Loading...
Let a + b + c = a b + b c + c a = 3 a b c = p . Then a , b , c are the roots of the equation x 3 − p x 2 + p x − 3 p = 0 . This equation will have real roots if − 2 7 × 9 p 2 + 1 8 × ( − p ) × p × ( − 3 p ) − 4 p 3 − 4 × ( − p 3 ) × ( − 3 p ) + p 2 × p 2 ≥ 0 . This yields ( p − 3 ) 2 ≤ 0 . Since ( p − 3 ) 2 can't be negative, therefore p − 3 = 0 or p = 3 . So 3 a b c = 3 or a b c = 1